Maritime boundary delimitation in Africa : developing a normative and institutional approach for the African Union Border Programme to manage maritime boundary delimitations - Tladi, Dire (University of Pretoria, 2024)
Thesis (LLD (International Law))--University of Pretoria, 2024.